Silencing Porcine CMAH and GGTA1 Genes Significantly Reduces Xenogeneic Consumption of Human Platelets by Porcine Livers. Issue 3 (March 2016) - Butler, James Russell; Paris, Leela L.; Blankenship, Ross L.; Sidner, Richard A.; Martens, Gregory R.; Ladowski, Joseph M.; Li, Ping; Estrada, Jose L.; Tector, Matthew; Tector, A. Joseph
Abstract : Background: A profound thrombocytopenia limits hepatic xenotransplantation in the pig-to-primate model. Porcine livers also have shown the ability to phagocytose human platelets in the absence of immune-mediated injury. Recently, inactivation of the porcine ASGR1 gene has been shown to decrease this phenomenon. Inactivating GGTA1 and CMAH genes has reduced the antibody-mediated barrier to xenotransplantation; herein, we describe the effect that these modifications have on xenogeneic consumption of human platelets in the absence of immune-mediated graft injury. Methods: Wild type (WT), ASGR1 −/−, GGTA1 −/−, and GGTA1 −/− CMAH −/− knockout pigs were compared for their xenogeneic hepatic consumption of human platelets. An in vitro assay was established to measure the association of human platelets with liver sinusoidal endothelial cells (LSECs) by immunohistochemistry. Perfusion models were used to measure human platelet uptake in livers from WT, ASGR1 −/−, GGTA1 −/−, and GGTA1 −/− CMAH −/− pigs. Results: GGTA1 −/−, CMAH −/− LSECs exhibited reduced levels of human platelet binding in vitro when compared with GGTA1 −/− and WT LSECs. In a continuous perfusion model, GGTA1 −/− CMAH −/− livers consumed fewer human platelets than GGTA1 −/− and WT livers. GGTA1 −/− CMAH −/− livers also consumed fewer human platelets than ASGR1 −/− livers in a single-pass model. Conclusions: Silencing the porcine carbohydrate genes necessary to avoid antibody-mediated rejection in a pig-to-human model also reduces the xenogeneic consumption of human platelets by the porcine liver. The combination of these genetic modifications may be an effective strategy to limit the thrombocytopenia associated with pig-to-human hepatic xenotransplantation. Abstract : The authors show that silencing the porcine carbohydrate genes CMAH and GGTA1 necessary to avoid antibody-mediated rejection in a pig-to-human model also reduces the xenogeneic consumption of human platelets by the porcine liver. Supplemental digital content is available in the text.